THE EFFECT OF THE GUIDED INQUIRY LEARNING MODEL ON STUDENT LEARNING OUTCOMES ON PLANT STRUCTURE AND FUNCTION MATERIAL IN GRADE VIII SMP NEGERI 12 MEDAN - Ramlan Silaban; Marpaung, Fytry Vebiola; Retno Dwi Suyanti; Mariati Purnama Simanjuntak; Aristo Hardinata (Jurnal Ilmu Pendidikan Indonesia, 2025)
Abstract: The guided inquiry learning model is one of the learning models that can improve student learning outcomes and student learning activities which is a learning model where teachers and students determine and formulate problems together, and students actively seek and find answers and draw their own conclusions. The purpose of the study was to determine the results of science learning on the material of Plant Structure and Function of class VIII students of SMP Negeri 12 Medan. To determine the Effect of the Guided Inquiry Learning Model on Student Learning Outcomes on the Material of Plant Structure and Function in Class VIII SMP Negeri 12 Medan. This research method uses a quantitative research method. The form of research is Quasi Experimental Design. The research design is a two group design. Data collection techniques were carried out using pre-research observations, interviews with Class VIII science teachers, conducting written tests on students in the form of questions, non-tests or questionnaires, observing student activities, and documentation in the form of research images and photos and value documents related to the results. Data analysis using hypothesis testing (one-sided t-test) and N-Gain testing. Based on the results of the t-test, the obtained t-value is 4.66> t-table 2.00. This means that the results of the hypothesis test t-count are greater than t-table. Next, based on the results of the N-gain test, the increase in learning outcomes in the control class was higher, namely 69% compared to the increase in student learning outcomes of 52%. So that the Guided Inquiry Learning Model applied to the experimental class in this study has an effect on student learning outcomes in the material on the Structure and Function of Plants in class VIII of SMP Negeri 12 Medan. Keywords: Learning